COMMERCIAL AND RESEARCH CLUSTERING OF AUGMENTED REALITY: DISCOURSES AND DIVIDES BETWEEN AR APPS AND APPLICATIONS - Heemsbergen, Luke; Cadman, Same (AoIR Selected Papers of Internet Research, 2021)
Although the majority of Augmented Reality (AR) scholarship is based in Computer Science disciplines, it is nevertheless important to consider emergent trends in AR discourses as research and development shifts from technology labs to media markets. While technical understandings of AR are necessary, they are insufficient to understand how networked spatial computing is augmenting everyday life. In response, this paper maps and compares two specific AR discourses for nodes of power and authority. First, it systematically reviews how AR research citations are shifting from science and technical foci to applied uses of AR via a systematic scientometric review. That work allows, among other insights, consideration of the extent disciplinary boundaries shaped how AR is understood and innovated. Second is contrasting these evolving patterns with current consumer exposure to AR via a critical technocultural discourse analysis (CTDA) of the presentation of phone-based AR apps available on the iOS App Store and Google Play. Comparative discussion of these inquiries adds to understandings of how AR is conceptualised in research and commercial discourses, and how these data might inform future research and practice in the socialisation of AR systems, media, and experience.